2013
DOI: 10.1371/journal.pone.0082428
|View full text |Cite
|
Sign up to set email alerts
|

Modified McKeown Minimally Invasive Esophagectomy for Esophageal Cancer: A 5-Year Retrospective Study of 142 Patients in a Single Institution

Abstract: BackgroundTo achieve decreased invasiveness and lower morbidity, minimally invasive esophagectomy (MIE) was introduced in 1997 for localized esophageal cancer. The combined thoracoscopic-laparoscopic esophagectomy (left neck anastomosis, defined as the McKeown MIE procedure) has been performed since 2007 at our institution. From 2007 to 2011, our institution subsequently evolved as a high-volume MIE center in China. We aim to share our experience with MIE, and have evaluated the outcomes of 142 patients.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
12
1
2
Order By: Relevance
“…However, in some large medical center with advanced medical technique, minimal invasive Ivor Lewis approach gained more popularity owning to lessened postoperative inflammatory reaction despite greater cost (20,21). There was no difference in 3-year OS between 2 approaches in our study.…”
Section: Cost Of Sweet Approach Was Lower Than That In Open Ivormentioning
confidence: 51%
“…However, in some large medical center with advanced medical technique, minimal invasive Ivor Lewis approach gained more popularity owning to lessened postoperative inflammatory reaction despite greater cost (20,21). There was no difference in 3-year OS between 2 approaches in our study.…”
Section: Cost Of Sweet Approach Was Lower Than That In Open Ivormentioning
confidence: 51%
“…A surgical trauma‐induced stress response can lead to the inhibition of cellular immunity in patients . With the development of minimally invasive endoscopic techniques, thoracoscopic esophageal resection results in less trauma, fewer complications, and better long‐term effects . In this study, traditional thoracotomy and minimally invasive endoscopic surgery were examined and the results showed that the two surgical procedures had the same effect on immune function; however long‐term differences were not studied.…”
Section: Discussionmentioning
confidence: 96%
“…Thoracoscopic surgery for esophageal cancer is often performed as a type of minimally invasive surgery (13)(14)(15)(16)(17). Although its importance as a minimally invasive procedure has been controversial to date, the reduction in blood loss that results from being able to recognize fine structure is a merit of thoracoscopic surgery (18).…”
Section: Discussionmentioning
confidence: 99%